(untitled) (Research, Society and Development, 2020)
This article aims to describe a case report of an immunocompetent adult patient with rotavirus infection, highlighting the points to be reviewed and the conducts performed, in order to include in the routine of health professionals more appropriate actions in cases of diarrhea. acute. The research was conducted qualitatively, with the direct collection of patient data, describing the events chronologically, aiming at a better understanding of the clinical picture and medical actions. The patient presented with diarrhea and colic, with worsening in 24 hours, being seen at the emergency room and later with specialist in infectology. Routine examinations, water and food support were performed during hospitalization, as well as symptomatic therapy and antibiotic therapy. Complementary examinations showed fecal rotavirus positivity, anti-HIV 1 - 2 negatives, co-culture and negative Clostridium difficile screening, and presence of liquid cecum-ascending dilation on computed tomography. During the evaluation period, a deficit in conduct points and decision-making concerns was visualized in patients with acute diarrheal diseases in a hospital environment. Thus, it is concluded that some protocols performed in ADD patients, such as the use of antibiotic therapy, should be closely monitored, as well as the need for greater attention to biosecurity and, consequently, the risk of new infections in the environment. in addition to the need for data to accompany the occurrence of rotavirus in adult patients, which target not only public units, which may serve to leverage preventive methodologies.